Berlin 2000. - Koch, Andreas; Müller, Ariane; Piechaczek, Benita; Reski, Gunter; Steinweg, Marcus (New York : Pace Wildenstein New York, 2009)
Bell, Dirk ; Bock, John ; Bonvicini, Monica ; Butzer, André ; Dahlem, Björn ; Eder, Martin ; Hammwöhner, Sebastian ; Jakob, Dani ; Vormstein, Gabriel ; Heinzmann, Thilo ; Helbig, Thomas ; Henneken, Uwe ; Hildebrandt, Gregor ; Hultén, Sofia ; Jörres, Klaus ; Junghanss, Lisa ; Kahrs, Johannes ; Kliem, Halina ; Kneihsl, Erwin ; Koch, Andreas ; Konrad, Karsten ; Kwade, Alicja ; Nicolai, Carsten ; Nicolai, Olaf ; Nitsche, Frank ; Pernice, Manfred ; Pflumm, Daniel ; Reski, Gunter ; Reyle, Anselm ; Strunz, Katja ; Rosemeyer, Jenny ; Scheibitz, Thomas ; Strauss, Peter F. ; Strunz, Katja ; Tokarski, Wawrzyniec ; Vormstein, Gabriel ; Weber, Suse ; Wendland, Tilman ; Zipp, Thomas ; Starship
biog. per kunstenaar
Engels
Berlin 2000. New York. Pace Wildenstein New York. 2009-03-07. 2009-04-18
boek
Keywords: Berlin; Duitsland